(untitled) (Research, Society and Development, 2021)
Inorganic bovine bone matrix (IBBM) is a biomaterial with proven osteoconductive functionalities. The objective of this study was to assess the in vivo bone regeneration functionalities of IBBM modified or not by an experimental MOE in sheep. MOE synthesis was performed by suspending nacre particles (0.05 g, diameters < 0.01 mm) in anhydrous acetic acid (pH 7, 5 mL, 25°C, 72 hours) using magnetic stirring. Polyethylene carriers (d= 5.0 mm, l= 10.0 mm, open ends) of negative control (sham) or experimental groups (IBBM or MOE-modified IBBM) were placed (n=3 conditions /animal; intramuscularly) adjacent to the lower spine of adult sheep (8 animals, » 45 Kg, 2 years old). Tissues were harvested (at 3 or 6 months) after implantation in preparation for histological (H), morphometrical (MM) and immunohistochemical analyses (IH; Wnt-3a, CD34, Vimentin and PREF-1). MM data were tested for normality and variance homogeneity using the Shapiro-Wilk and Levene tests, and Mann Whitney and Kruskal-Wallis, respectively. IM data were analyzed using two-way ANOVA and Tukey tests. Differences (p < 0.05) were observed between experimental groups (IBBM and IBBM+MOE at both 3 and 6 months) and controls (sham) for total area; Differences were not found for presence of remnant particles among experimental groups. The highest formation of bone was observed with IBBM+MOE (6-months). No differences (p > 0.05) were found on IM analysis (CD34, Vimentin, PREF-1, Wnt3a). Results indicated that experimental materials (IBBM+MOE) display promising functionalities. Additional studies are necessary to define biomaterials’ longitudinal effects and long-term biocompatibility properties.